2021
DOI: 10.3390/ani11051309
|View full text |Cite
|
Sign up to set email alerts
|

Caring for the Older Horse: A Conceptual Model of Owner Decision Making

Abstract: The number of aged horses in the UK has been growing over recent years, with many horses remaining active and being cared for into old age. However, increasing age is paralleled with a heightened risk of morbidity and mortality; therefore, owners of older horses must manage changes in their horse, making decisions about management and health care provision. In this paper, we discuss data collected from an open-access online discussion forum, where forum users sought advice arising from concerns about their old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 34 publications
(34 reference statements)
0
5
0
Order By: Relevance
“…To achieve this, an initial discussion using a topic guide (e.g., “could you tell us about a time when you have thought about a/your horse’s wellbeing?”; see Supplementary File S1 ), was followed by a group activity involving the comparison of pre-selected terms of interest displayed on a virtual whiteboard. Terms relevant to equine wellbeing and welfare were selected based on; their use by horse owners in previous equine studies [ 9 , 23 , 24 ], equine media, welfare science [ 3 , 25 ], and personal experience of the research team members. Terms comprised; quality of life, welfare, life worth living, wellbeing, happiness, good life and best life.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve this, an initial discussion using a topic guide (e.g., “could you tell us about a time when you have thought about a/your horse’s wellbeing?”; see Supplementary File S1 ), was followed by a group activity involving the comparison of pre-selected terms of interest displayed on a virtual whiteboard. Terms relevant to equine wellbeing and welfare were selected based on; their use by horse owners in previous equine studies [ 9 , 23 , 24 ], equine media, welfare science [ 3 , 25 ], and personal experience of the research team members. Terms comprised; quality of life, welfare, life worth living, wellbeing, happiness, good life and best life.…”
Section: Methodsmentioning
confidence: 99%
“…Research has found that horse owners and veterinary surgeons (veterinarians) use terminology such as quality of life, wellbeing and welfare when discussing topics including equine obesity, ageing and end-of-life care [ 7 , 8 , 9 ]. At times when views of a horse’s welfare or QoL were divergent, communication between veterinarians and horse owners/carers was reportedly challenging [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They seek support in health-related decisions for their horse from (in descending order) other horse owners, trainers, stable owners and internet/ friends/ family/ other [•]. There are three different types of typical decision-making procedures equestrians may follow: wait -observe -reassess/ provide medical care by themselves -reassess if necessary/ order a vet (mostly by phone) [19,27,28,39,40]. Aspects that need to be handled by the application: The equestrians may each follow individual life and health philosophies, whilst maintaining individual mental disease models (lay interpretations of diseases) [19,33].…”
Section: Discussionmentioning
confidence: 99%
“…Aspects to take into account while implementing: Equestrians show a better detection of behavioral changes of a known horse than veterinarians do [30,31]. They prefer their information and communication in a private, non-judgmental, lay-friendly and neutral or positive way, that is adjusted to their individual level of knowledge [15,16,20,21,24,26,27,30,[33][34][35][36]40]. When equestrians experience a possible health-related issue in their horse, they find themselves in an emotional, nervous and stressful situation [12].…”
Section: Discussionmentioning
confidence: 99%